PENGEMBANGAN HANDOUT MODEL SAINS TEKNOLOGI MASYARAKAT (STM) DI SMA 1 NEGERI ENAM LINGKUNG PADANG PARIAMAN - Erlinda, Nelfi; Lelfita, Lelfita (LP. Ma'arif Janggan Magetan, 2020)
This study aims to develop teaching materials in the form of high school physics technology handouts in the Science Technology Society (STM) model on straight motion material. This type of research is research and development that uses six steps of research, namely potential problems, information gathering, product design, design validation, design improvement, and product trials. The research instrument used was a questionnaire. Based on the analysis of the validation of the handout by the lecturer, an average value of 79% and an analysis of 88.5% of teachers showed that the handout was valid, and the practicality value of two teachers by 89% showed that the handout was very practical to use. Based on the analysis of the data above, it can be concluded that the handout of the STM model is valid and very practical to be used as teaching material for class X high school semester